THE ANALYSIS OF INFLUENCED FACTORS ON GER IN SENIOR HIGH SCHOOL (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims to examine and analyze the factors that affect the GER for high school / equivalent education in Indonesia in 2015-2019. The factors studied and analyzed in this study include poverty, number of education units (schools), student to teacher ratios, and per capita GRDP. The method used in this research is quantitative method. The type of data used is secondary data from the National Statistics Agency (BPS). While the analysis technique used is a panel data regression model that combines cross section data and time series data. Where the cross section data used covers 34 provinces in Indonesia, while the time series data used are from 2015-2019. The analysis in this study was carried out using the help of Microsoft Excel 2010 and Eviews 10. The results of the study found that partially poverty, student to teacher ratios, and per capita GRDP had an effect on GER, while the number of education units (schools) had no effect at all. Another case with simultaneous testing which results in all variables having an influence on GER.